Resistance of SARS‐CoV‐2 beta and gamma variants to plasma collected from Canadian blood donors during the spring of 2020. Issue 1 (22nd October 2021) - Drews, Steven J.; Abe, Kento T.; Hu, Queenie; Samson, Reuben; Gingras, Anne‐Claude; Colwill, Karen; Rathod, Bhavisha; Wang, Jenny; Fazel‐Zarandi, Mahya; Yi, Qi‐Long; Robinson, Alyssia; Wood, Heidi; et al.
Abstract: Background: This pilot study assesses the ability of plasma collected from Canadian blood donors in the first wave of the SARS‐CoV‐2 pandemic to neutralize later SARS‐CoV‐2 variants of concern (VOCs). Study design and methods: A repeated cross‐sectional design was used, and a random cross‐sectional sample of all available Canadian Blood Services retention samples (n = 1500/month) was drawn monthly for April and May of 2020. Qualitative IgG analysis was performed on aliquots of specimens using anti‐spike, anti‐receptor binding domain, and anti‐nucleocapsid protein enzyme‐linked immunosorbent assays as well as the Abbott Architect SARS CoV‐2 IgG assay (Abbott Laboratories) against the anti‐nucleocapsid protein. Selected plasma specimens were then assessed for neutralization against VOCs using pseudotyped lentivirus inhibition assays as well as plaque reduction neutralization test 50% (PRNT50 ). Results: Six specimens with a high neutralizing titer against wild‐type SARS‐CoV‐2 and three specimens with a low neutralizing titer against wild‐type SARS‐CoV‐2 were chosen for further analysis against VOCs. Four of six high neutralizing titer specimens had a reduced neutralizing capacity against beta VOCs by both neutralization methods. Three of six high neutralizing titer specimens had reduced neutralization capacity against gamma VOCs. Conclusions: This preliminary data can be used as a justification for limiting the use of first wave plasma products in upcoming clinical trials but cannot be used to speculate on general trends in the immunity of Canadian blood donors to SARS‐CoV‐2.